Fifty Ohm radio frequency heating treatment under controlled atmosphere for inactivating Escherichia coli ATCC 25922 inoculated on almond kernels. (April 2020) - Cheng, Teng; Ramaswamy, Hosahalli; Xu, Ruzhen; Liu, Qianqian; Lan, Ruange; Wang, Shaojin
Abstract: The purpose of the study was to validate effects of radio frequency (RF) heating under controlled atmosphere (CA) on thermal inactivation of E. coli ATCC 25922 in almond kernels. A 2.4 kW, 27.12 MHz, 50 Ω RF heating system was used to treat 1.5 kg size almond kernel samples with the adjusted moisture content of 8.0% wet basis under regular atmosphere (RA, 21% O2, 79% N2 ) and CA (2% O2, 20% CO2, 78% N2 ) conditions. The power level of 900 W under an electrode gap of 11.5 cm was used at the ramping stage for quick heating, and a maximum temperature difference of 3 °C in the inoculation area was achieved by continuing the RF heating at reduced power level during the 40 min holding stage. A 4-log reduction time under CA treatment was achieved with 21 ± 1 min holding at 75 ± 3 °C, reducing treatment time by 38% as compared with RA environment. The various quality attributes of treated samples remained within acceptable range based on nut industry standards. The RF heating under CA conditions may hold potential as an effective treatment method to control E. coli ATCC 25922 in raw almond kernels and be possibly extended for pasteurization applications. Highlights: CA assisted RF treatment protocols for pasteurizing almond kernels were developed. RF system provided stable gas tightness and concentrations under CA condition. Different RF power was used for ramp/hold to achieve the heating rate/uniformity. CA assisted RF heating produced >4-log E. coli reduction with good almond quality.